2021
DOI: 10.1101/2021.04.16.438110
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oncogenic PKA signaling stabilizes MYC oncoproteins via an aurora kinase A-dependent mechanism

Abstract: Genetic alterations that activate protein kinase A (PKA) signaling are found across many tumor types, but their downstream oncogenic mechanisms are poorly understood. We used global phosphoproteomics and kinome activity profiling to map the conserved signaling outputs driven by diverse genetic changes that activate PKA in human cancer, including melanoma and fibrolamellar carcinoma (FLC). We define two consensus networks of effectors downstream of PKA in cancer models. One is centered on RAS/MAPK components, a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Additionally, among PKACα (but not PKACβ) substrates, ENO1 and MBP1, which are splice variants described as Myc transcriptional repressors, have gained attention [85]. Some studies have observed increased levels of c-and N-Myc in cAMP stimulation conditions, while PKACα siRNA attenuates phosphorylation of its substrates and progressively decreases c-and N-Myc protein levels [55].…”
Section: Pkamentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, among PKACα (but not PKACβ) substrates, ENO1 and MBP1, which are splice variants described as Myc transcriptional repressors, have gained attention [85]. Some studies have observed increased levels of c-and N-Myc in cAMP stimulation conditions, while PKACα siRNA attenuates phosphorylation of its substrates and progressively decreases c-and N-Myc protein levels [55].…”
Section: Pkamentioning
confidence: 99%
“…The cell-cycle-dependent Aurora-A and Aurora-B form a circuit with Myc, in which Aurora primes the oncogenic program of Myc and vice versa [53,54]. Aurora-A is also involved in Myc modulation in PKA-dependent tumours [55]. Other kinases are crucial for Myc transcriptional activity (i.e., PIM and BRD4 [56][57][58]).…”
Section: Introductionmentioning
confidence: 99%